Glutamate receptors: desensitizing dimers. - Biggin, P (2002)
Recent structural studies show, not only how the desensitization of a ligand-gated ion channel with bound agonist can be rationalized in terms of subunit-subunit instability, but also how a previously unknown mode of interaction may provide clues into how the receptor is tetramerically assembled in vivo.